Doing the Job! Expectations of Police Recruits (Pre- and Post- Graduate Entry). (25th February 2023) - McCanney, John; Taylor, Julie
Abstract: This research explores the views of police recruits from cohorts pre and post the introduction of the graduate entry scheme. Recruits at the end of their initial training period were asked about their role and their expectations of policing. The views of recruits from these different cohorts are compared to understand whether the new graduate programme inculcated different views than the previous training programme. This research suggests that there are few differences between student officers who have completed the graduate training programme and those that did not. The findings suggest that there are deeply entrenched barriers and resistance to the change process. If change is to be achieved, it will require that the commitment of several stakeholders including the graduate officers themselves.